THE INFLUENCE OF MACRO VARIABLES ON FOREIGN DIRECT INVESTMENT (FDI) IN 8 ASEAN COUNTRIES - Choirunnisa, Rahma; Az Zakiyyah, Nurul Azizah (JIDE : Journal Of International Development Economics, 2023)
The title of the research is The Effect of Macro Variables on Foreign Direct Investment (FDI) in 8 Asean Countries. Tujaun research is to determine the influence of macro variables on foreign direct investment (FDI) in 8 Asean countries. The method of analysis in this study is quantitative method and uses secondary data from the World Bank. The data used consists of time series and cross-section data, so the panel data analysis method is used to analyse it. Panel data consists of space and time dimensions, combining the characteristics of cross-section data with time series data. Time series data was obtained from 2005-2022 with cross-section data on 8 ASEAN member countries, namely Indonesia, Malaysia, Singapore, Thailand, the Philippines, Brunei Darussalam, Vietnam, and Cambodia. The data analysis method used is quantitative analysis using panel data regression. This study uses panel data regression to determine differences between individuals or in each ASEAN country. The results showed that Foreign Direct Investment (FDI) is the flow of capital from abroad. FDI occurs when companies from one country invest directly in another country. FDI plays an important role in promoting economic growth, technology transfer, job creation, and productivity improvement in recipient countries. The decision to make foreign investment can be influenced by several macro variables, such as GDP, inflation, exchange rate, trade level, and labour force. This study uses panel data analysis method with data from 8 ASEAN countries in 2005-2022. The results of the study show that GDP and labour force have a positive effect on FDI in 8 ASEAN countries. Meanwhile, inflation, exchange rate, and trade profitability variables have no effect on FDI.